PENTINGNYA ANGGARAN KAS DALAM MENJAGA LIKUIDITAS DAN STABILITAS OPERASIONAL PERUSAHAAN - Ahmad Ramdhani Mungkur; Dinda Nurayuni Humaira; Nurhikmah Berasa; Dini Vientiany (INTERNATIONAL, Journal of Sharia Business Management, 2025)
Cash budgeting is an essential instrument in corporate financial management as it directly influences cash flow management, liquidity, and operational stability. This study aims to analyze the importance of cash budgets in maintaining liquidity and operational stability in companies. The research employs a qualitative approach using a descriptive method through a literature review. Data were collected from relevant academic sources, including accounting and financial management textbooks as well as national and international journal articles, particularly publications from 2021 to 2025. The findings indicate that a systematic and realistic cash budget enables companies to manage cash inflows and outflows more effectively, allowing short-term obligations to be met on time and reducing liquidity risk. Furthermore, cash budgeting functions as a preventive control tool that supports operational stability, especially in conditions of cash flow uncertainty. This study concludes that cash budgeting plays a strategic role as a planning, control, and decision-making tool in ensuring sustainable business operations. Therefore, companies are encouraged to continuously improve the preparation and evaluation of their cash budgets.